MODIFICATION OF WTER PUMP WIT GAS FUEL FOR PORTABLE SPRINKLER IRRIGATION SYSTEM - Mukhlis Tri Handoko (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Water pump that used by farmers for irrigation in general is ussualy gasoline pump. Using gasoline as a fuel will certainly add to the production costs, because the price of gasoline is more expensive and its availability are declining . Therefore, farmers should choose an alternative fuel that is cheaper to minimize production costs, for example is LPG fuel. The purpose of this research were to test the uniformity of flow performance, uniformity of distribution and application rate of portable sprinkler irrigation with a pump of gas-fire fuel pump. This research was conducted at the Marga Agung village, Jati Agung sub-district, South Lampung  in May-June 2015. Modified propulsion pump on the fuel system (carburettor) was replaced with a universal carburetor throat. Pump performance test conducted on a portable sprinkler irrigation systems (Tusi, 2013) using three variations of the pressure (1 bar, 1.25 bar and 1.5 bar). The tests conducted to determine coefficient of uniformity (CU), beam diameter, and weeting diameter. Modifications engine pump causes fuel consumption is more efficient, but the engine tends heat faster. The value of the test results obtained 1bar pressure by 32,2% CU, the discharge of 0.64 m3/h and wetting diameter of 15 m. Whereas at a pressure of 1.25 bar of 47,1% obtained CU, the discharge of 0.79 m3/h and a wetting diameter of 16 m. Varriation of pressure effected on pump performance test measurement results. The average needs of fuel gas was 0.47 kg per hour pump operation.Key word: modification, LPG, Portable Sprinkle, performance test